INTEGRASI INTERKONEKSI EKONOMI PANCASILA DAN EKONOMI ISLAM - Agus Salihin (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2020)
AbtracThis research was conducted in order to provide information about the integration of the Pancasila economic system and Islamic economics. An economic system based on Pancasila values is a joint effort based on family and mutual cooperation. Article 33 of the 1945 Constitution aims to maximize people's prosperity by means of the economy must be arranged based on economic democracy, where the prosperity of the people takes precedence over the prosperity of individuals or small groups. The purpose is in line with the word of God in sura QS Al-Hujurat verse 10 and QS. Al Maidah verse 2 and at-Taubah verse 71. Then in the Islamic view, Pancasila economy is an economic system that is in accordance with the spirit of Islamic Economics. Both systems have the same goal to realize social justice and economic prosperity for all humanity. Keywords: Pancasila Economy, Religion and Islamic Economy. Abstrak Penelitian ini dilakukan agar dapat memberikan informasi tentang integrase sistem ekonomi Pancasila dan ekonomi islam. Sistem ekonomi yang berlandaskan pada nilai-nilai pancasila, merupakan usaha bersama yang berasaskan kekeluargaan dan kegotong-royongan. Dalam Pasal 33 UUD 1945 bertujuan untuk kemakmuran rakyat secara maksimal dengan cara Perekonomian harus disusun berdasar demokrasi ekonomi, di mana kemakmuran masyarakat lebih diutamakan dari pada kemakmuran individu atau kelompok-kelompok kecil. Tujuan tersebut sejalan dengan firman allah dalam surah QS Al-Hujurat ayat 10 dan QS. Al Maidah ayat 2 dan at-Taubah ayat 71. Kemudian dalam pandangan Islam, ekonomi pancasila merupakan sistem perekonomian yang sesuai dengan semangat Ekonomi Islam. Kedua sistem tersebut memiliki kesamaan tujuan untuk mewujudkan keadilan sosial dan kesejahteraan ekonomi bagi seluruh umat manusia. Kata Kunci : Ekonomi Pancasila, Agama dan Ekonomi Islam.